Processos de patrimonialização no campo religioso brasileiro: o caso do Santo Daime - Dias, Maíra de Oliveira (2015)
This work seeks to establish an overview of heritage processes in Brazilian religious field, having as object the dynamic of heritage of the Santo Daime, through bibliographical and documentary research, and experiences in the field. For this, let‟s observe the relationship between culture, religion and heritage. We discuss the historical processes of patrimonialization in Brazilian religious field, starting the path by the Catholic Church and their built heritage listed as a historic place. Let‟s examine the Evangelic practice on the patrimonial field. And the landmark of the first Candomblé listed as a historic place and the relationship of african-Brazilian religions with intangible heritage. We finish this route with new religious movements and the ayahuasca religions. And watching the balance processes the Holy Daime'll analyze your asset dynamics, considering overturning, musealization and the collective application for registration of the ritual use of ayahuasca as a Brazilian intangible heritage, held in 2008. The understanding of religion as a cultural system of Clifford Geertz, field and habitus of Pierre Bourdieu, and a reflection on the secular nature of the State, contribute to the examination of the patrimony that we propose to analyze, realizing the sphere of heritage as a tool used in the disputes of the Brazilian religious field.